Brand Value, Asset Tangibility, Profitabilitas Dan Leverage Keuangan - I Made Sudana; Gusti Ayu Putu Wyndi Werdhianti (Jurnal Manajemen dan Bisnis Indonesia, 2017)
This study aimed to determine effect of brand value, asset tangibility, and profitability on financial leverage in Indonesia. This study used regression analysis to determine the effect of independent variables consisting of brand value, asset tangibility, and profitability on financial leverage.This study uses data sample of non-financial companies which are listed in Bursa Efek Indonesia during 2013-2016 period, the data is also collected from SWA magazine during 2013-2016 period to get brand value information. The analysis results show that brand value and asset tangibility are positive and significant to financial leverage. The higher brand value of the company, cause to higher creditur’s trust. The higher asset tangibility encourages higher collateral asset of the company to earn more loans. While profitability has negative effect, because the higher profitabiltiy will make the company prefer to use internal funding. Keywords: brand value, asset tangibility, leverage